Formulasi dan Evaluasi Zona Hambat Berbagai Sediaan Antijerawat dari Ekstrak Daun Kemangi (Ocimum Sanctum - Asyri Khoerunnisa; Dyanita Irene Susilo Putri; Farida Nur Aeni; Nia Yuniarsih (Jurnal Health Sains, 2022)
Basil leaves (Ocimum Sanctum) can live well in the wild or cultivated. So far, basil leaves (Ocimum Sanctum) are only used as a complementary ingredient in cooking. In fact, basil leaves (Ocimum Sanctum) have great potential to be used in cosmetics. These basil leaves also have active compounds, namely essential oils, alkaloids, saponins, flavonoids, steroids. Some of these tannins and phenols have anti-acne properties. In this study, we will discuss which preparations and at what concentration basil leaves are effective in inhibiting acne-causing bacteria (Staphylococcus Aureus). The research was conducted through a collection of journal data that has a purpose with the object of research and an explanation of several methods in the research is carried out. The results of the study concluded that the most effective preparation of basil extract in inhibiting acne-causing bacteria (Staphylococcus Aureus) was a cream preparation with an extract concentration of 45% with an inhibition zone of 25.05 mm.